2004
DOI: 10.7205/milmed.169.7.536
|View full text |Cite
|
Sign up to set email alerts
|

Preventive Health Behaviors, Health-Risk Behaviors, Physical Morbidity, and Health-Related Role Functioning Impairment in Veterans with Post-Traumatic Stress Disorder

Abstract: An examination of the relationships between health behaviors (preventive and risk-related), physician-diagnosed medical problems, role-functioning impairment because of physical morbidity, and post-traumatic stress disorder was conducted on a large cohort of consecutive treatment-seeking cases (N = 826) presenting to an outpatient Veterans Affairs post-traumatic stress disorder clinic. Results revealed that the sample rates of several medical conditions were markedly elevated when compared with general populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
93
1
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(100 citation statements)
references
References 19 publications
5
93
1
1
Order By: Relevance
“…Our results contrast Widome et al's findings (15) that found US veterans who smoked were more likely to be food-insecure. Veterans are more likely to report risky health behaviours compared with non-veterans which could also explain the discrepancy; yet since there were so few smokers in the current study, these results should be interpreted with caution (48,49) .…”
Section: Prevalence Of Household Food Insecuritymentioning
confidence: 70%
“…Our results contrast Widome et al's findings (15) that found US veterans who smoked were more likely to be food-insecure. Veterans are more likely to report risky health behaviours compared with non-veterans which could also explain the discrepancy; yet since there were so few smokers in the current study, these results should be interpreted with caution (48,49) .…”
Section: Prevalence Of Household Food Insecuritymentioning
confidence: 70%
“…Recent studies have found important linkages between smoking and certain anxiety disorders (Feldner, Babson, & Zvolensky, 2007a;Morissette, Tull, Gulliver, Kamholz, & Zimering, 2007;Patton, Carlin, Coffey, Wolfe, Hibbert, & Bowes, 1998; Zvolensky, Feldner, LeenFeldner, & McLeish, 2005 (Beckham et al, 1995;Breslau et al, 2003;Buckley et al, 2004;Feldner et al, 2007a). Recent controlled work supports the contention that PTSD is associated with earlier relapse compared to persons with no psychopathology (Zvolensky, Gibson et al, in press).…”
Section: Nih Public Accessmentioning
confidence: 99%
“…Other work suggests panic psychopathology is related to decreased success in quitting smoking (Lasser et al, 2000;Zvolensky & Bernstein, 2005;Zvolensky, Lejuez, Kahler, & Brown, 2004). Similarly, smoking rates are significantly greater among persons with, compared to those without, PTSD (Acierno et al, 2000;Acierno, Kilpatrick, Resnick, Saunders, & Best, 1996;Beckham et al, 1995;Buckley, Mozley, Bedard, Dewulf, & Greif, 2004). Investigations also have found that exposure to traumatic life events, particularly for those individuals with a PTSD diagnosis, is associated with an increase in smoking behavior (e.g., increasing the amount of cigarettes smoked per day; Breslau, Davis, & Schultz, 2003;Joseph, Yule, Williams, & Hodgkinson, 1993;Koenen et al, 2005;Perkonigg, Kessler, Storz, & Wittchen, 2000).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…6 Third, mental disorders and PTSD may cause biological and behavioral changes that increase the risk of physical disease, leading to greater medical utilization. 28 , 29,[12][13][14][30][31][32][33][34] Finally, there may be an increased likelihood of detection of medical problems in veterans with mental health problems, for example, through symptoms identified by mental health providers. Veterans with comorbid mental and physical problems may also be more likely to enroll in primary care, which could lead to increased utilization of other services, such as preventive screening through laboratory and diagnostic tests.…”
Section: Discussionmentioning
confidence: 99%